Children of Dune - Herbert, Frank, 1920-1986 (New York : ACE, 2019)
Paul Atreides' children, Leto II and Ghanima, are drawn into political and spiritual conflict as rival factions plot to shape the future of Arrakis and the empire.
Keywords: Science fiction; Brothers and sisters -- Fiction; Family relations -- Fiction